Sex differences in executive control: A systematic review of functional neuroimaging studies. (1st February 2021) - Gaillard, Alexandra; Fehring, Daniel J.; Rossell, Susan L.
Abstract: The number of studies investigating sex differences in executive functions, particularly those using human functional neuroimaging techniques, has risen dramatically in the past decade. However, the influences of sex on executive function are still underexplored and poorly characterized. To address this, we conducted a systematic literature review of functional neuroimaging studies investigating sex differences in three prominent executive control domains of cognitive set‐shifting, performance monitoring, and response inhibition. PubMed, Web of Science, and Scopus were systematically searched. Following the application of exclusion criteria, 21 studies were included, with a total of 677 females and 686 males. Ten of these studies were fMRI and PET, eight were EEG, and three were NIRS. At present, there is evidence for sex differences in the neural networks underlying all tasks of executive control included in this review suggesting males and females engage different strategies depending on task demands. There was one task exception, the 2‐Back task, which showed no sex differences. Due to methodological variability and the involvement of multiple neural networks, a simple overarching statement with regard to gender differences during executive control cannot be provided. As such, we discuss limitations within the current literature and methodological considerations that should be employed in future research. Importantly, sex differences in neural mechanisms are present in the majority of tasks assessed, and thus should not be ignored in future research. PROSPERO registration information: CRD42019124772. Abstract : Due to inconsistencies within the literature, we conducted a systematic review of functional neuroimaging studies investigating sex differences in executive control. Here, we show evidence for sex differences in the neural networks underlying tasks of executive control suggesting males and females engage different strategies depending on task demands. Due to methodological variability and involvement of multiple neural networks, a simple overarching statement cannot be provided.